E-learning using learning management system - Kulvietienė, Regina; Kulvietis, Genadijus; Šileikienė, Irma; Stankevič, Jelena (Lietuvos matematikos rinkinys, 2004)
Learning management systems (LMS) have become the mainstream technology underlying corporate training and the migration to e-learning. A great number of LMS provides integrated services such as the designing and development of on-line learning contents, the communication and collaboration between the learners and teachers, event scheduling, creation of test questions and test administration. LMS plays a key role in the e-learning environment.